PENYIMPANGAN DISIPLIN DI DUNIA PENDIDIKAN: MURID BERANI MELAWAN GURU - Gerasela; Syarfira; M. Zalva Zakira; Sani Safitri; Syarifuddin (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
The phenomenon of students who dare to fight teachers reflects the occurrence of serious disciplinary deviations in the world of education. This study aims to identify the factors causing this deviant behavior, as well as to analyze the role of teachers and parents in overcoming it. The method used is a literature study with a qualitative approach through content analysis of various relevant secondary sources. The results of the study indicate that behavior against teachers is influenced by internal factors such as students' personal character and traumatic experiences, as well as external factors such as family parenting patterns, peer influence, and exposure to negative content on social media. Disharmony in the socialization process and weak internalization of moral values ​​cause students to lose respect for the authority of teachers. In conclusion, synergy between teachers and parents is needed to strengthen character education in order to foster discipline, respect, and ethics in students.